Evaluasi Hasil Analisis FEM Manual dan Komputasi pada Struktur Rangka Ruang dan Portal 3D: Studi Literatur - Yuliawana, Elsa; Ali, Dang Fadhlan (Journal of Infrastructure and Construction Technology, 2024)
The Finite Element Method (FEM) is essential for analyzing complex structures, but a knowledge gap exists regarding result differences found between transparent manual/script methods (Excel, MATLAB) and automated commercial software (SAP2000, ETABS). This comparison is vital to address the need for transparent validation practices, especially for learning and design optimization. This study's objective is to compare key FEM outputs (nodal displacements, member forces, support reactions) using a literature review with a descriptive-analytic method. Main findings show two patterns: high consistency (results reported as "same" or <5% difference) for axial-dominated truss structures, attributed to decimal rounding ; however, large discrepancies were found specifically in bending moment components for portal frames. A data contradiction (10.89% displacement error vs. <0.1% force error) also highlighted manual implementation risks. It is concluded that FEM results are generally reliable. The practical implication is recommending transparent manual methods for learning purposes and algorithm validation , while commercial software is suited for complex professional design due to high computational efficiency.